Model of Innovation Capability and Competitive Advantage of Tourism SMEs During Covid-19 Pandemic (Universitas Negeri Semarang, 2022)
This study aimed to determine the role of innovation capability in mediating the internal factors of MSMEs towards competitive advantages during the Covid-19 pandemic. This study used a quantitative approach, involving 243 MSMEs in the tourism sector in Semarang Regency, Central Java, Indonesia as research respondents. Methods of data collection used a questionnaire. The data analysis method used partial least square structure analysis using SmartPLS. The results of this study found a strong role of innovation capability in mediating entrepreneurial orientation and social capital on the competitive advantage of tourism MSMEs. There was a positive and significant effect between innovation capability and competitive advantage with an estimated weight of 45 percent of innovation capability which could explain the variation of competitive advantage. The competitive advantage of MSMEs during the pandemic was determined by social capital and also entrepreneurial orientation. The recommendation that can be given from this research is the model of innovation capability should be more exploration for research in another sector of MSMEs